Roles of the Cell Surface Architecture of Bacteroides and Bifidobacterium in the Gut Colonization - Nishiyama, Keita; Yokoi, Tatsunari; Sugiyama, Makoto; Osawa, Ro; Mukai, Takao; Okada, Nobuhiko (Frontiers in Microbiology, 2021)
There are numerous bacteria reside within the mammalian gastrointestinal tract. Among the intestinal bacteria, Akkermansia, Bacteroides, Bifidobacterium, and Ruminocuccus closely interact with the intestinal mucus layer and are, therefore, known as mucosal bacteria. Mucosal bacteria use host or dietary glycans for colonization via adhesion, allowing access to the carbon source that the host’s nutrients provide. Cell wall or membrane proteins, polysaccharides, and extracellular vesicles facilitate these mucosal bacteria-host interactions. Recent studies revealed that the physiological properties of Bacteroides and Bifidobacterium significantly change in the presence of co-existing symbiotic bacteria or markedly differ with the spatial distribution in the mucosal niche. These recently discovered strategic colonization processes are important for understanding the survival of bacteria in the gut. In this review, first, we introduce the experimental models used to study host-bacteria interactions, and then we highlight the latest discoveries on the colonization properties of mucosal bacteria, focusing on the roles of the cell surface architecture regarding Bacteroides and Bifidobacterium.